Reuso de efluentes no processo industrial de siderurgia - Santos, Anderson Baptista dos [UNESP] (2014)
The use of water and consequently its reuse are receiving a lot of attention around the World. This report has analyzed some possibilities for reusing the flowing out of a metallurgical company, specifically in a water treatment station from a rolling mill which receives the water from the Paraiba do Sul river and the effluents is discharged in the Surdos river. This report has also analyzed the need of adjustment to attend CONAMA 357/2005, CONAMA 430/2011 and Decree 8.468/1976 once the stream which receives this effluent has a low flow. Because of this, the treatment for this effluent has to obey strict parameter of quality, and the disposal has to be lower than the values fixed in the resolutions and decrees. While treating the effluent we have identified the possibility for reuse instead of just dismiss. The task has presented some challenges to the reuse application in industries that produce its own potable water. To compare the tax charged by SABESP, in Vale do Paraíba region, and the cost of internal water production has a 8 times difference in cost. Then only small work with low investment can became viable. As in the case of reusing water to wash the floor, scrap cooling, reuse in toilets and urinal, showing return only after five years